Exploring Whistleblowing Intention and Retaliation Measurement Instrument Using Rasch Model - Larasati, Meita; Wulan, Mulyaning (Journal of Accounting Research, Organization and Economics, 2024)
Objective This study aims to explore instruments used to measure both the intent to become a whistleblower and the perception of retaliation, and to explore the demographics of the sample using the Rasch model.Design/Methodology The results suggest that women are more likely to become whistleblowers than are men, regardless of the consequences.Results The paper concludes that both the basis of the cases against the banks and the purpose of large fines are open to question.Research limitations/implications More importantly, the results demonstrate that use of Rasch modeling can empirically validate instruments for measuring both the tendency to become whistleblowers and the effect of retaliation on whistleblowers.Novelty/Originality This study rated the likelihood of their reporting various violations of accounting principles.